2020
DOI: 10.3390/app10124227
|View full text |Cite
|
Sign up to set email alerts
|

Crack Growth and Energy Release Rate for an Angled Crack under Mixed Mode Loading

Abstract: The evaluation of energy release rate with angle is still a challenging task in metal crack propagation analysis, especially for the mixed Mode I-II-III loading situation. In this paper, the energy release rate associated with stress intensity factors at an arbitrary angle under mixed mode loadings has been investigated using both a numerical method and theoretical derivation. A relatively simple and precise numerical method was established through a series of spatial-inclined ellipses in Mode I-II and ellipso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Even though all the right-angled zigzag patterns offer high durability that can be measurable after 30-time stretching (see figure 4(a)), a half thickness pattern (2 mm wide) displayed three times higher relative resistance than thicker patterns (over 4 mm wide). Both non-right angled zigzag patterns generated fail to measure the electrical resistance after 30-time stretching due to the imbalance of x-and y-stress (explained in figure 3(b)) that was proved by previous computational studies [38,39].…”
Section: Optimal Pattern Selection On Spandexmentioning
confidence: 84%
“…Even though all the right-angled zigzag patterns offer high durability that can be measurable after 30-time stretching (see figure 4(a)), a half thickness pattern (2 mm wide) displayed three times higher relative resistance than thicker patterns (over 4 mm wide). Both non-right angled zigzag patterns generated fail to measure the electrical resistance after 30-time stretching due to the imbalance of x-and y-stress (explained in figure 3(b)) that was proved by previous computational studies [38,39].…”
Section: Optimal Pattern Selection On Spandexmentioning
confidence: 84%
“…He has shown that the type of inclusion does influence on fatigue crack propagation due to the energy release rate. Utilising the concepts of the energy release rate associated with the stress field around the inclusions [49], it has been proven that an important source of crack is voids near the inclusions [50][51][52]. All these mechanisms together with the larger effective sizes of inclusions in transverse fatigue specimens facilitates the fatigue crack initiation and also propagation [53] in transverse specimens compared to that of longitudinal specimens and hence reducing the fatigue limit.…”
Section: Fractographic Observationsmentioning
confidence: 99%
“…The rotating material axes investigate the anisotropy of material and help to approves the new finite element methods [19] such as the scaled boundary finite element method [20], fractal two-level finite element method [21], the element-free Galerkin method with the fractal finite element method [22] and the ES-FEM [16]. The deviation of the principal direction of a crack is defined as kinking of the crack which can be seen as the first step of the propagation, evaluated either with the ERR [23][24][25][26] or more often with the stress intensity factor [27]. It's taken into account for the fatigue crack growth [28] the effect of the T-stress [27] and different other cases.…”
Section: Introductionmentioning
confidence: 99%